2017
DOI: 10.1016/j.rmed.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics associated with clinical severity and inflammatory phenotype of naturally occurring virus-induced exacerbations of asthma in adults

Abstract: Background In experimental studies viral infections have been shown to induce type 2 inflammation in asthmatics, but whether this is a feature of naturally occurring virus-induced asthma exacerbations is unknown. Thymic stromal lymphopoietin (TSLP) released from the airway epithelium in response to damage, has been suggested as a link between viral infection and type 2 inflammation, but the role of TSLP in asthma exacerbations is unknown. Objective To assess whether type 2 inflammation, as measured by sputum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
0
16
0
3
Order By: Relevance
“…The researchers found three variants of the HRV: HRV-A, HRV-B, and HRV-C, with HRV-C being the most virulent for severe asthma exacerbations [15]. Other studies conducted in Japan, France, and Australia have also identified rhinovirus as the most common viral culprit for asthma exacerbations [28,[60][61][62]. White blood cells and neutrophil counts were significantly higher in patients with all HRV variants versus those who were negative for HRV (12.38 ± 5.13 vs. 10.77 ± 4.87 and 64.70 ± 20.27 vs. 56.44 ± 21.95, respectively) [15].…”
Section: Rhinovirusmentioning
confidence: 99%
See 4 more Smart Citations
“…The researchers found three variants of the HRV: HRV-A, HRV-B, and HRV-C, with HRV-C being the most virulent for severe asthma exacerbations [15]. Other studies conducted in Japan, France, and Australia have also identified rhinovirus as the most common viral culprit for asthma exacerbations [28,[60][61][62]. White blood cells and neutrophil counts were significantly higher in patients with all HRV variants versus those who were negative for HRV (12.38 ± 5.13 vs. 10.77 ± 4.87 and 64.70 ± 20.27 vs. 56.44 ± 21.95, respectively) [15].…”
Section: Rhinovirusmentioning
confidence: 99%
“…Zheng et al [15] conducted one of the numerous studies that demonstrated that human rhinovirus (HRV) was the most common viral microbe to induce an asthma exacerbation in children [60][61][62]. Zheng and colleagues collected data from 143 inpatient children with asthma exacerbations, 131 outpatients, including 88 patients with asthma exacerbations, and 43 controls with stable asthma [15].…”
Section: Rhinovirusmentioning
confidence: 99%
See 3 more Smart Citations